Feigned HIV infection/AIDS: malingering and Munchausen's syndrome. Issue 5 (October 1994) - Churchill, D R; De Cock, K M; Miller, R F
Abstract : Feigned HIV infection or acquired immunodeficiency syndrome (AIDS), in which people mimic infection with or disease due to HIV, accounted for 1.7% of admissions to our specialist HIV unit in Central London over a 5 year period. Of 12 patients with feigned HIV/AIDS, 11 were HIV antibody-negative, and one refused testing. Presenting histories were sometimes grandiose, unusually tragic, or unlikely in relation to the patients' healthy appearance, and often included admissions to other specialist HIV units. Substance abuse was suspected in over half of the patients described, a higher frequency than that observed in our HIV-infected patient population. The possibility of feigned HIV/AIDS should be remembered in persons with self-reported HIV infection. Recognition of this condition is important to avoid costly and potentially dangerous investigation and therapy.